Playing with food waste: Experimenting with ethical entanglements in the Anthropocene. Issue 7 (October 2019) - Turner, Bethaney
Anthropocentric thinking produces fractured ecological perspectives that perpetuate destructive, wasteful behaviours. Recognition of the relational entanglements of humans and more-than-humans, particularly through our everyday visceral encounters with food, may be able to encourage ethical ecological thinking and practices that lay the foundations for more sustainable lifestyles. This paper explores possible ways embodied, convivial and experimental interactions with food waste and its avoidance – along with the various assemblages through which it both acts and is enacted – can support recognition of the entangled relations in which humans and more-than-humans co-become. Excess food, its prevention, reuse and disposal, requires management through intimate human bodily engagements where the very vitality of food is inescapable. The affective force of these necessarily multispecies interactions –which can prompt desires for both attachment and detachment and manifest in a myriad of forms of togetherness – exposes mutual vulnerabilities in living together. Through analysis of ethnographic data gathered from 38 food-producing gardeners and Alternative Food Networks (AFNs) participants in the Australian Capital Territory, this paper maps out how experimental, playful interactions with leftover, surplus or wasted food could contribute to the development of the skills and competencies necessary for adapting to our contingent futures. Encounters with excess food are shown to be capable of assisting in training sensitivities to become attuned and responsive to our more-than-human entanglements and mutual vulnerabilities. This responsive attunement can induce and support ethico-political beliefs and practices that have the potential to disrupt anthropocentric thinking.